Kansas steer futurities: an economic analysis of retained ownership and a summary of cattle performance from 1974-1988 - Simms, D.; Mintert, J.; Maddux, A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The performance, carcass characteristics, and economic data from over 6,200 steers entered in Kansas Steer Futurities from 1974 through 1988 were summarized to evaluate production trends and profitability. The steers' delivery weights, final weights, and frame scores increased over the 14-year period, while daily gain was essentially unchanged. The quality grade, fat thickness, and yield grade all decreased slightly. Ribeye area increased slightly, but ribeye area per unit of carcass remained constant over the years. Based on the delivery weight of the steers, price, normal production relationships, and estimated production costs, we estimate that net returns over cash costs for the cow/calf phase have averaged $5.97 per cow unit from 1974 through 1988, with losses in 7 of those years. Correspondingly, steers in the futurities have been profitable in 10 of the 14 years, with an estimated average return of $38.43. Thus, retaining ownership should be a viable marketing alternative for progressive Kansas cattle producers.
Keywords: Beef; Futurity; Retained ownership; Marketing